Triple oxygen isotope geochemistry - Bindeman, Ilya; Pack, Andreas 1970- (Mineralogical Society of America, 2021)
Volume 86 of Reviews in Mineralogy and Geochemistry concentrates on understanding the variations among ratios of the three isotopes of oxygen, with primary emphasis on terrestrial systems. Triple oxygen isotope variations may be related to large, mass-independent fractionation effects such observed in the Earth atmosphere or may be small and related to minute variations due to purely mass-dependent processes. Recent advancements in analytical resolution now allow for the identification of processes and distinct reservoirs that were formerly hidden in the paradigm of a "single terrestrial fractionation line". New, high-resolution measurements are accompanied by advances in theoretical calculations that dovetail with empirical calibrations and applications throughout this volume. 14 chapters span a wide range of subjects: from ab-initio theoretical approaches to observation of triple oxygen isotope variations in the Earth litho-, hydro- and atmosphere.